An Overview of Ocean Climate Change Indicators: Sea Surface Temperature, Ocean Heat Content, Ocean pH, Dissolved Oxygen Concentration, Arctic Sea Ice Extent, Thickness and Volume, Sea Level and Strength of the AMOC (Atlantic Meridional Overturning Circulation) - Garcia-Soto, Carlos; Cheng, Lijing; Caesar, Levke; Schmidtko, S.; Jewett, Elizabeth B.; Cheripka, Alicia; Rigor, Ignatius; Caballero, Ainhoa; Chiba, Sanae; Báez, Jose Carlos; Zielinski, Tymon; Abraham, John Patrick (Frontiers in Marine Science, 2021)
Global ocean physical and chemical trends are reviewed using seven key ocean climate change indicators: (i) Sea Surface Temperature, (ii) Ocean Heat Content, (iii) Ocean pH, (iv) Dissolved Oxygen concentration, (v) Arctic Sea Ice extent, thickness and volume (vi) Sea Level and (vii) the strength of the Atlantic Meridional Overturning Circulation (AMOC). The globally averaged ocean surface temperature shows a mean warming trend of 0.062 ± 0.013oC/decade over the last 120 years. During the last decade the rate of ocean surface warming has accelerated to 0.280 ± 0.068oC/decade (4.5 times higher). Ocean Heat Content in the upper 2000m shows a warming rate of 0.35 ± 0.08W/m2 in the period 1955-2019. The mean increase rate of OHC during the last decade is twice as high (0.70 ± 0.07W/m2) as the long term mean. Global surface ocean pH has declined by approximately 0.1 since the industrial revolution. By the end of this century ocean pH is projected to decline additionally by 0.1 to 0.4 pH units. The time of emergence of the signal varies from 8 to 15 years for open ocean sites, and 16 to 41 years for coastal sites. Global dissolved oxygen levels have decreased by 4.8 petamoles or 2% in the last 5 decades, with profound impacts on local and basin scale habitats. Arctic sea ice extent is declining by -13.1% per decade during summer and by -2.6 % per decade during winter. The combined trends of sea ice extent and sea ice thickness indicate that the volume of non-seasonal Arctic Sea Ice has decreased by 75% since 1979 to 2020. Global mean sea level has increased in the period 1993-2019 at a mean rate of 3.15 ± 0.3 mm/yr and is experiencing an acceleration of ~ 0.084 (0.06-0.10) mm/yr2. Satellite altimetry also reveals strong regional variability in the rates of sea level change. Proxies of the evolution of the Atlantic Meridional Overturning Circulation indicate that AMOC is at its weakest for several hundreds of years and has been slowing down during the last century. A final visual summary of key ocean climate change indicators is provided.